Differences in the Rearing System Toward Bali Cattle Gastrointestinal Helminths Infestation in Prafi District, Manokwari Regency, West Papua Province, Indonesia - ., Purwaningsih; Widayati, I; Nurhayati, D; Baaka, A (KnE Life Sciences, 2019)
Helminthic disease is a disease that attacks cattle at various ages. The cattlerearing influence the development of parasitic disease agents. The objective of this study was carried out to determine the extent to which level of parasites infestation towards different cattle rearing system through examination of cattle feces. Coprological techniques, simple flotation, and simple sedimentation were used to detect gastrointestinal helminths in Bali cattle. A total of 369 rectal fecal samples were collected from Bali cattle on semi-intensively reared, and non-intensively reared in Prafi District, Manokwari Regency, West Papua Province, Indonesia. Fecal samples were used for qualitative and quantitative coprological examination. Eggs worms were identified based on morphology. Meanwhile, the relationship between rearing system to the prevalence of helminthic diseases was analyzed by Chi-square test. Descriptive analyses results showed that the overall prevalence was 57.45 % of gastrointestinal (GI) helminths and the prevalent helminthes eggs identified were Strongyle (22.22 %), Strongyloides (0.81 %), Fasciola (34.96 %), Paramphistomum (10.03 %), Toxocara (5.96 %), Trichuris (2.44 %), and Moniezia (0.81 %). The result showed that there was no association (P < 0.05) between rearing system and the prevalence of gastrointestinal helminth infestation. Keywords: Bali cattle, Gastrointestinal helminths, Manokwari Regency, Prevalence, Rearing system